Optimizing children's hand orthosis design: A study on contact pressure distribution using FSR sensors - Dhaval Patel; Ivaylo Mitev; Thomas Rockenbauer; Thomas Antretter; Sandra Schloegl; Margit Lang (Materials & Design)
The design and comfort of hand orthoses for children are crucial for effective therapeutic outcomes. This research primarily aims to measure the contact force between the hand and orthoses in children under 10 years old and use this data as a loading condition for topology optimization to reduce high-pressure areas, thereby enhancing wear comfort. Force Sensing Resistor (FSR) sensors were employed to record the contact force at 16 specific points on the orthoses using a voltage divider circuit with two different setups: the Teensy 3.5 chip board for 12-bit precision and the Elegoo Mega 2560 chip board for 10-bit precision. These force measurements were compared to existing data from an adult to highlight differences in pressure distribution. Additionally, the study demonstrates the feasibility of integrating precise sensor data into computational models for optimizing medical device designs. While this data could also be utilized in future research for sizing adjustments to optimize the soft padding materials within the orthoses for improved comfort, this aspect is not the primary focus of the current study. The results underscore the importance of developing orthotic designs tailored to pediatric users, informed by precise contact force measurements, to mitigate critical pressure sores and improve overall comfort.